Compression Promotes the Osteogenic Differentiation of Human Periodontal Ligament Stem Cells by Regulating METTL14-mediated IGF1 - Wu, Zengbo (Current Stem Cell Research & Therapy, 2024)
Background and Objectives: Orthodontic treatment involves the application of mechanical force to induce periodontal tissue remodeling and ultimately promote tooth movement. It is essential to study the response mechanisms of human periodontal ligament stem cells (hPDLSCs) to improve orthodontic treatment. Methods: In this study, hPDLSCs treated with compressive force were used to simulate orthodontic treatment. Cell viability and cell death were assessed using the CCK-8 assay and TUNEL staining. Alkaline phosphatase (ALP) and alizarin red staining were performed to evaluate osteogenic differentiation. The binding relationship between IGF1 and METTL14 was assessed using RIP and dual-luciferase reporter assays. Results: The compressive force treatment promoted the viability and osteogenic differentiation of hPDLSCs. Additionally, m6A and METTL14 levels in hPDLSCs increased after compressive force treatment, whereas METTL14 knockdown decreased cell viability and inhibited the osteogenic differentiation of hPDLSCs treated with compressive force. Furthermore, the upregulation of METTL14 increased m6A levels, mRNA stability, and IGF1 expression. RIP and dual-luciferase reporter assays confirmed the interaction between METTL14 and IGF1. Furthermore, rescue experiments demonstrated that IGF1 overexpression reversed the effects of METTL14 knockdown in hPDLSCs treated with compressive force. Conclusions: In conclusion, this study demonstrated that compressive force promotes cell viability and osteogenic differentiation of hPDLSCs by regulating IGF1 levels mediated by METTL14.
Keywords: periodontal ligament